Impacto da gravidade da síndrome da apneia obstrutiva do sono sobre às respostas cardiovasculares e metabólicas ao teste cardiopulmonar de exercício em idosos com hipertensão arterial: um estudo observacional - Freire Júnior, Pedro Crisóstomo Alves (2021)
Background: the aging process causes autonomic and endothelial dysfunction, such as which are associated with arterial hypertension and obstructive sleep apnea syndrome (OSAS). These diseases, when associated, can exacerbate sympathetic hyperactivity and attenuate the heart rate of recovery, both disorders are reported to have worse cardiovascular outcomes. Aim: to evaluate the impact of the severity of obstructive sleep apnea on the cardiovascular and metabolic responses to the cardiopulmonary exercise test in elderly people with arterial hypertension. Methods: thirty nine hypertensive elderly people with OSAS were included, who were allocated into 3 groups, according to the apnea / hypopnea index (AHI): mild OSA (AHI ≥ 5 and ≤15 events / h; n = 15), OSAS moderate (AHI > 15 and ≤ 30 events / h; n = 18) and severe OSAS (AHI > 30 events / h; n = 9). All underwent CPET, polysomnography and completed the sleep quality questionnaire (PSQI). The Shapiro-Wilk and Levene tests were used to assess data distribution and sample homogeneity. One-way ANOVA, Kruskal-Wallis and Spearman's Correlation tests were used. The level of significance accepted was p ≤0.05. Results: there were no statistical differences in oxygen consumption, oxygen pulse, minute ventilation, ventilatory efficiency, respiratory changes, maximum and expected heart rate and blood pressure between the elderly groups assessed during the CPET (p > 0.05 for all comparisons). The elderly with severe OSAS had a lower HRrec1' response delta compared to the moderate OSAS group (18.3 ± 4.9 vs 13.7 ± 6.9 bpm; p = 0.041) and mild OSAS (18.2 ± 3.4 vs 13.7 ± 6.9 bpm; p = 0.042). There are no significant differences in ΔFCrec2' among the elderly with severe OSAS compared to the moderate OSAS group (26.4 ± 7.4 vs 29.0 ± 5.1 bpm, respectively; p = 0.059) and in relation to the group Mild OSAS (26.4 ± 7.4 vs 30.7 ± 4.7 bpm, respectively; p = 0.094). There is no correlation between the AHI and ΔFCrec1' (r = - 0.210; p = 0.198) and ΔFCrec2' (r = - 0.114; p = 0.488). Elderly people with severe OSAS present worse sleep quality, compared to mild OSAS (9.5 ± 3.11 vs 4.3 ± 0.96; respectively, p = 0.018). Similarly, it is also observed that the elderly with moderate OSAS are poor sleepers compared to mild OSAS (7.0 ± 1.52 vs 4.3 ± 0.96; respectively, p = 0.019). On the other hand, there is no significant difference between groups of elderly people with severe and moderate OSAS (9.5 ± 3.11 vs 7.0 ± 1.52; respectively, p = 0.133). Conclusion: the severity of obstructive sleep apnea attenuates parasympathetic reactivation and worsens the subjective quality of sleep in elderly hypertensive patients, but does not alter the exercise capacity and hemodynamic responses during maximum physical effort.